Use of Akaike information criteria for model selection and inference. An application to assess prevention of gastrointestinal parasitism and respiratory mortality of Guinean goats in Kolda, Senegal - Lancelot, R.; Lesnoff, Matthieu; McDermott, John J. (Elsevier, 2002)
A field experiment was carried out in Kolda (southern Senegal) from July 1986 to July 1988. Its goals were to: (1) describe the patterns of mortality of female Guinean goats by age, season and year; (2) assess preventive measures against respiratory diseases and gastrointestinal parasitism in reducing mortality; and (3) estimate the overall impact of these measures on survival to 1 year of age. Preventive measures for respiratory disease included vaccination against peste des petits ruminants (PPR) and pneumonic pasteurellosis (Pasteurella multocida types A and D). Control of gastrointestinal parasites was by deworming does with morantel (7.5 mg kg-1, three times during the rainy season). The effects of vaccines and deworming were tested in a randomised factorial field experiment with villages being the experimental units. A total of 19 villages, 113 goat herds and 1458 goats were included in the study. Generalised linear models of survival for five cohorts of goats (defined by five different birth seasons) used a binomial assumption for the response distribution and a complementary log–log link. Explanatory variables included age, season, year, vaccination, deworming and their interactions. A complex a priori model was built on the basis of previous epidemiological knowledge; a purposively selected set of simpler models was compared to this full model by the Akaike information criterion (AIC) and derived statistics. Inference on 1-year survival and treatment effects accounted for model-selection uncertainty. It was carried out with a bootstrap procedure and used information from the whole set of selected models. Large variations in mortality by year and season were observed but no regular seasonal pattern was apparent. Mortality probabilities of kids in dewormed groups decreased quickly after birth, but remained elevated up to 9 months of age in the non-dewormed groups. Deworming lowered the risk of mortality. Vaccination alone was not protective (except during an observed outbreak of PPR).